2015
DOI: 10.1038/bjc.2015.102
|View full text |Cite
|
Sign up to set email alerts
|

miR-367 promotes epithelial-to-mesenchymal transition and invasion of pancreatic ductal adenocarcinoma cells by targeting the Smad7-TGF-β signalling pathway

Abstract: Background:Aberrant Smad7 expression contributes to the invasion and metastasis of pancreatic cancer cells. However, the potential mechanism underlying aberrant Smad7 expression in human pancreatic ductal adenocarcinoma (PDAC) remains largely unknown.Methods:Bioinformatic prediction programmes and luciferase reporter assay were used to identify microRNAs regulating Smad7. The association between miR-367 expression and the overall survival of PDAC patients was evaluated by Kaplan–Meier analysis. The effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 34 publications
1
69
0
Order By: Relevance
“…In NSCLC, elevated miR-367 levels are associated with shorter postoperative relapse-free periods. miR-367 also enhances hepatocellular carcinoma cell proliferation and invasion by regulating PTEN expression (Meng et al, 2016), and promotes pancreatic cancer invasion in vitro and metastasis in vivo through targeting of the Smad7/ TGF-β signaling pathway (Zhu et al, 2015). In addition, this miRNA suppresses Adriamycininduced apoptosis of osteosarcoma cells by targeting KLF4 (Wang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In NSCLC, elevated miR-367 levels are associated with shorter postoperative relapse-free periods. miR-367 also enhances hepatocellular carcinoma cell proliferation and invasion by regulating PTEN expression (Meng et al, 2016), and promotes pancreatic cancer invasion in vitro and metastasis in vivo through targeting of the Smad7/ TGF-β signaling pathway (Zhu et al, 2015). In addition, this miRNA suppresses Adriamycininduced apoptosis of osteosarcoma cells by targeting KLF4 (Wang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…miR-367 has recently been identified as a novel tumor-related miRNA in colon cancer (Chae et al, 2013), breast cancer (Zhang et al, 2011), medulloblastoma (Kaid et al, 2015), esophageal squamous cell carcinoma (ESCC; Sun et al, 2016), gastric cancer (Bin et al, 2015), osteosarcoma (Wang et al, 2016), hepatocellular carcinoma (Meng et al, 2016), glioma (Guan et al, 2015), pancreatic ductal adenocarcinoma (Zhu et al, 2015), non-small cell lung cancer (NSCLC; Campayo et al, 2013), and cervical carcinoma (Cai et al, 2013). Modulation of miR-367 expression can affect several aspects of cancer cell behavior, including proliferation, apoptosis, invasion, and epithelial-to-mesenchymal transition.…”
Section: Introductionmentioning
confidence: 99%
“…All experimental procedures involving animals were approved by the ethics Committee of the First affiliated hospital of Xi'an Jiaotong university. antagomir-367-and antagomir-NCtreated H1299 cells (1x10 7 ) were suspended in 150 µl pBS, and then subcutaneously inoculated into the flank of nude mouse. After two weeks, tumor volume (V) was determined by measuring tumor length (L) and width (W) once every three days with a Vernier caliper, and then calculated in accordance with the formula: V = (L x W 2 ) x 0.5.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have mainly investigated the functions of miR-367 in embryonic stem cell self-renewal and the maintain of pluripotency (4). Recent studies revealed that miR-367 participates in the tumorigenesis of various types of cancers, such as hepatocellular carcinoma (5), medulloblastoma (6) and pancreatic cancer (7). In contrast, in the study of gastric carcinoma, miR-367 inhibited cell migration and invasion, and its expression in cancer tissues was much lower than that in normal stomach tissues (8).…”
Section: Introductionmentioning
confidence: 99%
“…Down-regulation of SMAD7 is highly correlated with tumor metastasis and poor prognosis in human pancreatic cancer. Zhu et al (2015) established that miR-367 acts as a suppressor of SMAD7 in human pancreatic cancer by direct targeting and suppressing SMAD7 expression at both mRNA and protein levels. MiR-367 expression level is negatively correlated with SMAD7, and low level of SMAD7 is associated poor prognosis of PDAC.…”
Section: Tgf-β Signalingmentioning
confidence: 99%